Editor’s note - Sebolai, Kabelo (Journal for Language Teaching, 2022)
I am very pleased to release volume 56, number 1 (2022) of the Journal for Language Teaching, our first open access issue. Our sincere gratitude goes to the Stellenbosch University Library for agreeing to be the host for our journal on an Open Journal Systems (OJS/PKP) platform. We are confident that the platform will contribute immensely towards boosting the journal’s visibility and readership worldwide. A total of eight articles, dealing with language teaching matters from a variety of perspectives are covered in this volume. The first is by Drennan and Keyser, an evaluation of the impact of a discipline-specific writing intervention for Law students at the Free State University. The study for the article took place in the context of widespread concerns about inadequate witing skills among university students and their resultant failure to complete their studies in scheduled time. The findings show that the intervention impacted positively on the writing ability of the participants and confirm the currently dominant view that academic literacy endeavours in general should be driven in line with the nuances of students’ disciplinary contexts. The second article by Maphoto, focuses on the value of constructive feedback in writing instruction at an open-distance learning university in South Africa. The article approaches its focus from the perspective of learners, since they are the ones expected to improve the quality of their writing as a result of the quality of the feedback they receive. The article’s findings reveal a discouraging picture of the quality of this feedback and the students’ ability to understand it. This is very unfortunate, considering the limited opportunity that students in a long-distance university such as this one have for a face to face interaction with their lecturers. The impact of this situation on student success and throughput rates is obvious. Mather’s article relates to Maphoto’s in terms of its focus on writing instruction, albeit at a lower level of education. The article focuses on how the way a teacher positions themselves in relation to their learners determines whether students benefit from writing instruction or not. It deals with Grade 6 boys in particular because of the findings reported by the author from earlier studies that boys tend to underperform in national and international language assessments. The article’s main finding is that in terms of the way they position themselves and their learners, teachers do not always scaffold effectively to help students learn how to write. This is also unfortunate, considering that learner achievement has proven to benefit a lot from proper scaffolding in all language teaching contexts. The article by Van Dyk and Adrianatos deals with referencing-related challenges that first year students typically struggle with in academic writing. It utilizes the data collected from a multilevel, multi-genre, multi-language learner corpus of South African languages for academic purposes compiled on behalf of the South African Centre for Digital Language Resources (SADiLaR), to perform an error analysis of typical referencing errors and the frequency of specific kinds of referencing errors in the academic writing of students. The difference that this article makes lies, as its authors put it, in its moving beyond “having an idea of what errors they make”, to an in-depth corpus-based investigation of these errors. Like the rest of the articles focusing on academic writing in this volume, the value added by Van Dyk and Adrianatos’ article to the development of writing ability among first year students is worth the effort. The next article by Ndu, Tshotsho and Cekiso deals with a crucial topic in language teaching in general and the teaching of English as an additional language in particular. This is the need to take into account, the diverse intelligences and cognitive levels that learners bring to class and to put measures in place to accommodate this diversity in language teaching. To this end, the article investigated rural high school teachers’ perceptions of the application of socio-cultural and multiple intelligences approaches in their teaching of learners of English as an additional language, to determine the scope of the need for teacher training in differentiated instruction. In the context of education in South Africa particularly, learners’ intelligences have been impacted on by their diverse socio-economic backgrounds, so much so that the importance for teachers to be familiar with ways to differentiate their teaching approaches cannot be overlooked. The article by Munyaradzi and Manyike focuses on the controversial issue of English as a dominant language of teaching and learning in South Africa, where the majority of those served by education are non-native speakers of this language. The article’s finding is not new; as a primary medium of instruction, English diminishes effective teaching and learning for students to whom it is not a first language. This is a reminder that resources need to be provided for African indigenous languages to be developed into academic languages and that English support for students is necessary for as long as it continues to serve as a language of teaching and learning. The article by Sefotho deals with the important issue of multilingualism at all levels of education in South Africa. It laments the absence of a systematic approach on how schools should promote multilingualism, even though the promotion of multilingualism is at the centre of the Language in Education Policy of the country. The article proposes a concept called Ubuntu Translanguaging as a solution to the lack of systematicity in the promotion of multilingualism. The lack of a systematic way to promote multilingualism is attributed to the evidence revealed by the article, of a misinterpretation of the Language in Education Policy among teachers, the supposed key role players in the implementation of this policy. The last article by Mokoena deals with the impact of Covid-19 on effective teaching in English First Additional Language classrooms in rural areas. Specifically, it focuses on the impact of the safety measures put in place to curb the spread of the pandemic, on learner-centred teaching in these schools. Measures such as the wearing of masks and social distancing would have an obviously negative impact on the extent to which teachers and learners could express themselves clearly and collaborate closely in teaching and learning contexts as it was the case before the arrival of Covid-19. This article uses qualitative research data to confirm that this was indeed the case. Kabelo Sebolai September 2022